Isolation of extra-cellular vesicles in the context of pancreatic adenocarcinomas: Addition of one stringent filtration step improves recovery of specific microRNAs. - Yi-Fan Xu (Public Library of Science (PLoS), 2021)
microRNAs (miRNA) in extracellular vesicles (EVs) have been investigated as potential biomarkers for pancreatic ductal adenocarcinoma (PDAC). However, a mixed population of EVs is often obtained using conventional exosome isolation methods for biomarker development. EVs are derived from different cellular processes and present in various sizes, therefore miRNA expression among them is undoubtedly different. We developed a simple protocol utilizing sequential filtration and ultracentrifugation to separate PDAC EVs into three groups, one with an average diameter of more than 220 nm, named operational 3 (OP3); one with average diameters between 100-220 nm, named operational 2 (OP2); and another with average diameters around 100 nm, named operational 1 (OP1)). EVs were isolated from conditioned cell culture media and plasma of human PDAC xenograft mice and early stage PDAC patients, and verified by nanoparticle tracking, western blot, and electronic microscopy. We demonstrate that exosome specific markers are only enriched in the OP1 group. qRT-PCR analysis of miRNA expression in EVs from PDAC cells revealed that expression of miR-196a and miR-1246, two previously identified miRNAs highly enriched in PDAC cell-derived exosomes, is significantly elevated in the OP1 group relative to the other EV groups. This was confirmed using plasma EVs from PDAC xenograft mice and patients with localized PDAC. Our results indicate that OP1 can be utilized for the identification of circulating EV miRNA signatures as potential biomarkers for PDAC.